2012
DOI: 10.1590/s0100-736x2012000200007
|View full text |Cite
|
Sign up to set email alerts
|

Intercorrência entre leucose enzoótica e brucelose em búfalos (Bubalus bubalis) em sistema de produção extensivo

Abstract: Pesq. Vet. Bras. 32(2):131-134, fevereiro 2012 131 RESUMO.-Objetivou-se com este estudo avaliar a intercorrência entre leucose enzoótica e brucelose em búfalos (Bubalus bubalis) em sistema de produção extensivo, pelo estabelecimento da prevalência de bubalinos reagentes às provas diagnósticas especíϐicas. Foram analisados sorologicamente 232 animais, pela técnica de imunodifusão dupla em gel de agarose para diagnóstico de leucose enzoótica e o teste do antígeno acidiϐicado tamponado, seguida pelos testes conϐi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 2 publications
0
11
0
3
Order By: Relevance
“…O diagnóstico utilizado para brucelose em bubalinos tem sido baseado nas pesquisas de anticorpos por métodos sorológicos (Mathias et al 1998, Fosgate et al 2002, Molnár et al 2002, Nasir et al 2004, Bastianetto et al 2005, Chaves et al 2012, Silva et al 2014, Pereira et al 2015. Para demonstrar a presença desta bacteria a reação em cadeira da polimerase em tempo real (qPCR) detecta o DNA de Brucella spp.…”
Section: Introductionunclassified
“…O diagnóstico utilizado para brucelose em bubalinos tem sido baseado nas pesquisas de anticorpos por métodos sorológicos (Mathias et al 1998, Fosgate et al 2002, Molnár et al 2002, Nasir et al 2004, Bastianetto et al 2005, Chaves et al 2012, Silva et al 2014, Pereira et al 2015. Para demonstrar a presença desta bacteria a reação em cadeira da polimerase em tempo real (qPCR) detecta o DNA de Brucella spp.…”
Section: Introductionunclassified
“…Borriello et al (2006) reported a potential risk for humans after the consumption of milk and dairy products from buffaloes infected with Brucella abortus. Chaves et al (2012) in Maranhão and Calderón et al (2010) in Colombia reported the prevalence of brucellosis in buffaloes as 5.18% and 3%, respectively. The low frequency (1.5%) of brucellosis that was found in this study may be due to the number of bovine brucellosis control actions that are conducted by the animal defense service of Paraíba, including the inspection of vaccinations and animal movement control.…”
Section: Resultsmentioning
confidence: 94%
“…The second most common serotype was Pomona, whose maintenance host is the pig (FAINE et al, 1999), which also suggests contact with these species in breeding consortiums. The Canicola serotype, which was named the third most frequent, is usually associated with dogs as a maintenance host (FAINE et al, 1999).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations